Evaluasi Program Pengurangan Emisi Limbah Industri Dalam Upaya Mencapai Target Perlindungan Lingkungan - Maghrobi Ilham Rahmansyah; Mohammad Yahya Nur Firdaus; Diota Cahya Muhajir; Moch. Bayu Septian; Denny Oktavina Radianto (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Evaluation of industrial waste emission reduction programs is a critical step in efforts to achieve environmental protection targets. These programs aim to reduce the negative impact of industrial pollution on the environment and human health. This research aims to evaluate the effectiveness of the industrial waste emission reduction program that has been carried out in an effort to achieve the environmental protection targets that have been set. The journal research method with the literature review method is an approach used to collect, evaluate, and synthesize information from various relevant literature sources. The effectiveness of industrial waste emission reduction programs is very important to maintain environmental sustainability. These programs aim to reduce the negative impact of industrial pollution on the environment and human health. Evaluation of the effectiveness of these programs is crucial to ensure that emissions reduction efforts achieve the desired results (Ikhtiarin et al, 2023). In this evaluation, it is necessary to consider an analysis of the type of emissions targeted, external factors that influence the effectiveness of the program, and the social and economic impacts of the program. Apart from that, the application of technology and innovation to reduce emissions and industry compliance with emission reduction programs are also important factors. Community participation and involvement also plays a role in supporting the success of industrial waste emission reduction programs, by increasing awareness and active participation of the community in efforts to reduce waste emissions.